Edukasi Ukhuwah vs Flexing di bulan Puasa dan menjelang Idulfitri bagi Generasi Z - M. Rozali; Rismayanti Rismayanti; Larasati Nur Kharomah; Arya Prandana (Universitas Pahlawan Tuanku Tambusai, 2026)
Ramadan and Eid al-Fitr, originally sacred moments for strengthening ukhuwah (brotherhood) and fostering self-restraint, are currently facing a shift in meaning due to the rise of